Constraints, mechanisms, and strategies for industry-education integration in vocational education: An empirical study - Bo Yu; Ruipu Li; Siyuan Zhang; Peng Mao; Chun Xu; Jing Shi; Gang Wu (PLoS ONE, 2025)
Identifying the constraints hindering industry-education integration (IEI) in vocational education is a critical prerequisite for promoting its high-quality development. However, existing research has yet to establish a systematic solution to this core issue. Therefore, this study takes Shenzhen, China, as a case study and adopts an empirical research approach to construct an analytical framework of “factor identification-mechanism analysis-strategy formulation,” aiming to thoroughly investigate the key constraints on IEI development in vocational education. First, based on a literature review and questionnaire survey, the study identifies 12 critical constraining factors of IEI. Subsequently, through expert interviews and Interpretative Structural Modelling (ISM), it reveals the underlying mechanisms of these constraints, classifying the 12 factors into five hierarchical levels. These factors form 16 constraint pathways, with inadequate policies, weak foundations for school-enterprise collaboration, insufficient institutional commitment, and ineffective communication mechanisms identified as critical bottom-level factors. These indirectly influence intermediate factors such as hardware/software conditions, alignment of talent cultivation philosophies, education-market demand matching, collaboration channel efficiency, and stakeholder interest fulfillment. Consequently, they diminish corporate engagement enthusiasm, blur responsibility-rights boundaries between stakeholders, and dampen faculty participation motivation, ultimately impeding IEI progress. Finally, the study proposes targeted countermeasures, emphasizing tripartite collaboration among the government, vocational institutions, and enterprises. Key strategies include strengthening legal safeguards, consolidating industry-education collaboration foundations, and proactively fulfilling educational responsibilities. The findings resolve the dilemmas constraining IEI development, providing policymakers with evidence-based references and offering practical guidance for deeper collaboration between vocational institutions and enterprises. This study holds significant theoretical and practical value for advancing high-quality vocational education.